2017
DOI: 10.1111/jir.12373
|View full text |Cite
|
Sign up to set email alerts
|

Parental attributions for positive behaviours in children with autism spectrum disorder

Abstract: Interventions that alter parental attributions may offer pathways to increase closeness in the parent-child relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
(47 reference statements)
0
6
0
2
Order By: Relevance
“…Our findings have some clinical implications, as they suggest that supporting parents to read their children’s mental lives in less negative ways may help with feelings of stress. Interventions that seek to alter or correct negative attributions may thus offer a means to reduce parenting stress (Bussanich et al 2017 ; Hassall and Rose 2005 ; Johnston and Ohan 2005 ). Research has addressed the topic of parental attributions towards challenging behavior in the field of child abuse and emotional/behavioral disorders (e.g., Dadds et al 2003 ; Sawrikar et al 2018 ), but research in this area could also be beneficial for the field of developmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings have some clinical implications, as they suggest that supporting parents to read their children’s mental lives in less negative ways may help with feelings of stress. Interventions that seek to alter or correct negative attributions may thus offer a means to reduce parenting stress (Bussanich et al 2017 ; Hassall and Rose 2005 ; Johnston and Ohan 2005 ). Research has addressed the topic of parental attributions towards challenging behavior in the field of child abuse and emotional/behavioral disorders (e.g., Dadds et al 2003 ; Sawrikar et al 2018 ), but research in this area could also be beneficial for the field of developmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Social impairments can impact the interactions that students with ASD have with their parents. Bussanich, Hartley, and Bolt [22] completed a study on the attributional style of positive, expected behaviors in parents of individuals with ASD. The researchers found that the father of a student with ASD with a higher educational level saw their child's behavior as controllable, versus the mother's which did not have this association.…”
Section: Autism Spectrum Disordersmentioning
confidence: 99%
“…Play provides physical, motor and cognitive support (Hamm, 2005;Yamaner, 2001). (Aldred, 2018;Bradshaw, 2017;Bussanich, 2017;Dammann, 2017;Green, 2010;Kasari, 2010;Parsons, 2017;Pickles, 2016;Stadnick, 2015).…”
Section: Summary Introductionmentioning
confidence: 99%
“…Oyunun bu gücü -çeşitli gelişim özelliklere sahip tüm çocukların gelişim ve öğrenme süreçlerinde etkili olduğu ifade edilir. Otizm spektrum bozukluğu (OSB) olan çocukların güçlendirilmesinde de oyunun oldukça değerli olduğunu gösteren araştırma sonuçları vardır (Aldred, 2018;Bradshaw, 2017;Bussanich, 2017;Dammann, 2017;Green, 2010;Kasari, 2010;Parsons, 2017;Pickles, 2016;Stadnick, 2015).…”
Section: Introductionunclassified
See 1 more Smart Citation